IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN MUTU PEMBELAJARAN AKIDAH AKHLAK DI MADRASAH ALIYAH RAUDHATUL HUDA AL ISLAMY SIDOMULYO KECAMATAN NEGRIKATON KABUPATEN PESAWARAN TAHUN PELAJARAN 2021/2022 - Rita Mustikawati; Afif Ansori; Endang Ekowati (UNISAN JURNAL, 2022)
Implementation of Madrasah Management contains two aspects of study, the first is a study in the concept of an approach in running a business, especially in the education segment. In achieving or getting something, there must be a discrepancy with the expected initial goal. The problem is the gap between the expectation of something and the reality that exists. Based on the description of the background of the problem above, it can be revealed that efforts to improve the quality of learning for Aqidah Akhlak subjects require the implementation of madrasa-based management concepts. Through Madrasah Aliyah Raudhatul Huda Al Islamy Sidomulyo, Negrikaton District, Pesawaran Regency as one of the institutions that uses this approach, the problem can be formulated as follows: How is the implementation of madrasa-based management in an effort to improve the quality of learning Aqidah Akhlak subjects at Madrasah Aliyah Raudhatul Huda Al Islamy Sidomulyo Negrikaton District, Pesawaran Regency? This type of research is a qualitative research, namely a research procedure that produces descriptive data in the form of written or spoken words from the people and actors being observed, directed at the background of the individual as a whole (holistic) without isolating individuals and organizations in variables but viewing them as part of a whole. Based on the overall description that has been stated above, several conclusions can be drawn, including: In general, the implementation of madrasa-based management at Madrasah Aliyah Raudhatul Huda Al Islamy Sidomulyo, Negrikaton District, Pesawaran Regency includes: curriculum management and teaching programs, education staff management, student management, financial management, facilities and infrastructure management and madrasah relationship management with the community. Basically, the implementation of madrasa-based management in these various fields has been going well. Keywords: Quality of Learning and Management Implementation